Understanding Digital Capital as a Factor of Transformation of Professional Communities - V. Е. Yarmak (Дискурс)
Introduction. To date, in the scientific discourse, an approach to the definition of digital capital as an object of research in sociology is only being formed. Sociological analysis is important for the study of digital capital because it is able to reveal its specifics, features, material and non-material components.Methodology and sources. The study and theorization of digital capital is based on theoretical and methodological positions and studies of the processes of digitalization and digital capital proposed by researchers earlier. Based on this, the author proposed her own definition of digital capital and research methodology and conducted a pilot empirical study.Results and discussion. It is revealed that, on the one hand, the development of society under the influence of digitalization and the presence of digital capital among representatives of various socio-demographic and professional groups contributes to the development of society. But on the other hand, the simplification of structural processes in connection with the introduction of digital technologies entails a number of objective problems: a shortage of specialists with the necessary competencies, a decrease in the quality of qualifications existing specialists, inequality among professional groups, unemployment, etc.Conclusion. In one way or another, digitalization has affected either the working conditions or influenced the transformation of the profession, including new specialties and requirements. The main advantage of digitalization is to increase the productivity of the enterprise by reducing the time required to develop a new product, release it to the market and deliver it to the consumer, as well as to optimize the company's resources, which increases the efficiency of its work as a whole. Respondents employed at IT enterprises noted that the process of digitalization minimally affected their field of activity, since it was always “in numbers” anyway. At the same time, the IT profession has really transformed. This lies in the fact, that earlier it included only those who are engaged, for example, in programming, and now this profession includes everyone who is somehow connected with a digital product.